Impact of inactivated COVID-19 vaccination on female ovarian reserve: a propensity score-matched retrospective cohort study - Huang, Jialyu; Guan, Tianshu; Tian, Lifeng; Xia, Leizhen; Xu, Dingfei; Wu, Xingwu; Huang, Lingling; Chen, Mengyi; Fang, Zheng; Xiong, Chaoyi; Nie, Liju; Wang, Shuang; et al. (Frontiers in Immunology, 2023)
Purpose: To explore the impact of inactivated COVID-19 vaccination on ovarian reserve as assessed by serum anti-Müllerian hormone (AMH) concentration. Methods: A total of 3160 women were included in this single-center retrospective cohort study between June 2021 and October 2022. Vaccination information were collected from official immunization records available in personal mobile apps. Serum AMH was qualified by electrochemiluminescence immunoassay and compared with previous measurement data within three years. Women were categorized to the vaccinated group if they received two doses of inactivated COVID-19 vaccines (Sinopharm or Sinovac) between AMH tests (n = 488), and to the control group if not vaccinated (n = 2672). Propensity score matching and multivariate linear regression were performed to control for potential confounders. The main outcome measures were the numeric AMH change and percentage AMH change between the two tests. Results: There were 474 women left in each group after matching all baseline characteristics. The mean interval from the first to second AMH measurement was 508.0 ± 250.2 and 507.5 ± 253.6 days for vaccinated and unvaccinated women, respectively (P = 0.680). Both groups had a significant AMH decrease in the second test compared with the first test (P = 0.001). However, the second AMH level remained comparable between groups (3.26 ± 2.80 vs. 3.24 ± 2.61 ng/mL, P = 0.757). Similarly, no significant differences were observed in numerical (-0.14 ± 1.32 vs. -0.20 ± 1.56 ng/mL, P = 0.945) and percentage (2.33 ± 58.65 vs. 0.35 ± 48.42 %, P = 0.777) AMH changes. The results were consistent in sub-analyses for women aged <35 and ≥35 years. There were also no significant differences when vaccinated women were divided according to the time interval after vaccination: ≤30, 31–60, 61–90, and ≥91 days. Conclusion: Our study provides the first evidence that inactivated COVID-19 vaccination has no measurable detrimental effect on ovarian reserve, regardless of female age and vaccination interval. This reassuring finding adds to the safety evidence of COVID-19 vaccine in fertility, and should be useful to promote vaccine acceptance. Multicenter prospective cohort studies are needed to validate our conclusion.